2021
DOI: 10.1016/j.rechem.2021.100199
|View full text |Cite
|
Sign up to set email alerts
|

In silico investigation of phytoconstituents of medicinal herb ‘Piper Longum’ against SARS-CoV-2 by molecular docking and molecular dynamics analysis

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

5
5

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 52 publications
0
25
0
Order By: Relevance
“…These proteases are responsible for the replication of the virus in the human body and enclosing ubiquitin and ISG15 into the host cell preventing regulation of protein circulation in human cells, respectively (Mengist 2020 ; Barretto 2005 ). It causes swift death of the healthy cells and rapid fall in the immunity of the patient (Shree 2022 ; Lakhera 2021 , Altay 2020 ). In this study, we have taken 3D coordinates of M pro (PDB ID: 6LU7) and PL pro (PDB ID: 4OVZ) in their native states derived by X-ray crystallography from protein data bank with resolution 2.16 Å and 2.50 Å, respectively, as drug target macromolecule.…”
Section: Methodsmentioning
confidence: 99%
“…These proteases are responsible for the replication of the virus in the human body and enclosing ubiquitin and ISG15 into the host cell preventing regulation of protein circulation in human cells, respectively (Mengist 2020 ; Barretto 2005 ). It causes swift death of the healthy cells and rapid fall in the immunity of the patient (Shree 2022 ; Lakhera 2021 , Altay 2020 ). In this study, we have taken 3D coordinates of M pro (PDB ID: 6LU7) and PL pro (PDB ID: 4OVZ) in their native states derived by X-ray crystallography from protein data bank with resolution 2.16 Å and 2.50 Å, respectively, as drug target macromolecule.…”
Section: Methodsmentioning
confidence: 99%
“…The in-silico modeling is generally used computer-aided drug designing (CADD) technique that is preferred by the chemists and researchers for the evaluation of the drug-like character of the selected systems. Thousands of research works had been reported based on CADD like Feverfew and Piper longum which were used against the M pro and PL pro of COVID-19 [17,18], Tridax procumbens was used against MCM7 breast cancer [19], Blumea mollis was used as an anti-fungal candidate [20], Bjerkandera adusta was used against Proteostasis Network Modules [21], and Curcuma Fig. 1 Morphology of Clitoria ternatea plant longa (Turmeric) and Cymbopogon citratus (lemongrass) as lipoxygenase inhibitor [22].…”
Section: Highlightsmentioning
confidence: 99%
“…Optimized geometry helps in nding the net polarity of the molecule by the means of dipole moment. More the dipole moment, more the compound will be polarizable (Lakhera et al 2021;Visscher and Geerke 2019;Rana et al 2017). In the present case, the selected EAA Histidine (5.58 Debye) have the maximum dipole moment as compared to Isoleucine (1.65 Debye), Leucine (1.85 Debye), Lysine (0.88 Debye), Methionine (0.96 Debye), Phenylalanine (1.62 Debye), Threonine (2.50 Debye), Tryptophan (2.95 Debye), and Valine (1.31 Debye) (SD 1).…”
Section: Structurementioning
confidence: 99%